An Exploratory Study of Requirements Engineering Practices in Indonesia – Part 1: Concepts and Problems - Kurniawan, Tri A.; Rusdianto, Denny S.; Brata, Adam H.; Amalia, Faizatul; Santoso, Angga; Raharjo, Dini I. N. R. P. (Faculty of Computer Science (FILKOM) Brawijaya University, 2019)
This paper provides the first part of statistical research findings of an exploratory study of the requirements engineering practices implemented in software development processes in Indonesia. This first part attempts to reveal facts regarding concepts and problems exist in such requirements engineering practices. We developed a comprehensive online questionnaire consisting of both closed- and open-ended questions in order to capture such facts. We invited 158 participant candidates representing industry and higher education institutions, however, 31 of them joined our web-based survey. Results show that most of participants confirm that requirements engineering must be properly performed in order to clearly define the valid product. They, however, encounter some difficulties in implementing requirements engineering concepts in practice due to a tight schedule, inappropriate skill of the analysts and inadequate tools used.